Modern experience in the use of organizational & economic mechanism of regulation of the process of fundamental scientific knowledge’ production - Al-Ghazali, Ameen Saif Ali (Współczesne Problemy Zarządzania, 2020)
The subject of the research is cross-country comparisons of models of organizational and economic mechanism of regulation (OEMR) of processes of production of fundamental scientific knowledge (FSK) during the organization of basic scientific research (FSR) by academic institutions. The ultimate goal of the development of OEMR and the task of conducting FSR is formulated. The hypothesis about the possibility of effective implementation of OEMR FSR in the case of clear definition of subjects and forms of regulation is substantiated. The thesis on the expediency of structuring OEMR FSR with the separation of levels of systematization of scientific knowledge as an object of regulation, conceptual components, subject content of FSK subsystems, elements of the FSK formation cycle in the process of solving partial cognitive problems of fundamental scientific theories (FNT), functional levels principles and criteria for ensuring the effectiveness of non-monotonic abductive FSR, distinguishing tools for providing analytical and regulatory functions. The research method is to generalize the features of national models of public regulation of FSR, which differ in proportions and combination of methods of direct administration and create conditions for independent choice of subjects of directions and options of R&D under the influence of dynamic updating of axiological concept of FSR. There are methods of using power competencies to form and use basic research competencies of FSR subjects in the field of FSR production – direct administrative influence, formal-mechanistic solidarity of subjects within the functioning of academic research networks, external value orientation and motivation of FSR subjects. The list of methods of stimulating innovative renewal of practical and transformative competencies in the field of FSK functioning includes methods of indirect regulatory influence, contractual solidarity of FSR subjects within the functioning of voluntary/temporary professional research networks, internal value and identification orientation of FSR subjects, global standards of practical and transformative competencies of FSR subjects in the field of FSK formation. The result of the study is to identify the main types of models with a detailed description of the practical principles of the implementation of FSR in the countries that represent them. The difference in the potential of FSR implementation depends on the ability of national institutions to organize the processes of conducting cyclical program research in order to increase the background design knowledge of the most universal nature.